PENDAMPINGAN TERHADAP SISWA-SISWI SMA SWASTA KRISTEN YPKPM AMBON UNTUK PENGAMBILAN DATA DALAM MENGHITUNG KANDUNGAN KARBON DI KOTA AMBON - Herman Siruru; Irwanto Irwanto; Iskar Iskar; Leonard Dantje Liliefna; Donald Dias; Noel Bernard (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Initiated by the Christian Private High School, YPKPM Ambon, the strengthening of the Pancasila Student Profile, through one of its programs, motivated the students to be involved in the efforts to reduce the effects of global warming. This activity obtained assistance from the university staffs, especially those who have experiences in the measurements of carbon stocks in forests and other land uses. By the end of this activity, the student could figure out factors that caused global warming and were able to calculate the amount of the carbon stocks stored in various types of land covers. The results of the activity showed that the calculation of the above-surface carbon in the Urban Forest area, for each type, were as follows: dense vegetation (104.57 tons/ha), sparse vegetation (20.09 tons/ha) and Imperata cylindrica land (0.52 tons/ha), therefore, the absorption of carbon dioxide (CO2) stored in Dense Vegetation were 383.43 tons/ha, Sparse Vegetation were 73.68 tons/ha and Imperata cylindrica land were 1.90 tons/ha. This activity also suggested that urban forest areas with Imperata cylindrica closure type needed a land rehabilitation activity such as planting trees.